Effect of clamshell: \b sand ratio on production of bricks for load bearing wall in IBS construction - Prakash Jeyamani (School of Environmental Engineering, University Malaysia Perlis, 2012)
This study was carried out to investigate the potential of using clamshell with different percentages as sand replacement in sand brick with ratio 1:3, an its potential to be used as load bearing wall. Clam shell is abundantly available in Malaysia as a by-product from seafood industry and also upon decease of mollusks life span. This waste is not yet exploited in other applications except that it has been used in small-scaled craft production. The mineral composition of the clam shell which consist of Calcium (Ca), Carbon (C), Magnesium (Mg) and Silica (Si) which is similar to that sand, gravel and cement suggest its potential as an alternative material in sand brick production for masonry wall. This research is an attempt to use clam shell as part of the sand in brick composition for a better load bearing brick. 128 piece of Cement brick with dimensions of 225 mm in length, 105 mm in width, and 75 mm in depth were prepared and been divided into four group with an equal numbers according to different type of testing. These bricks replaces sand by clamshell; 20 %, 10 %, 5 % and 0 % as the control mixture. The water to cement ratio of 0.50 and cement to aggregates ratio 1:3 were standardized to all of the sample mixtures. Compressive strength testing results, the 20% Clamshell mixture shows the highest compressive strength compared to other mixture at indoor condition while control brick shows the lowest compressive strength. According to the BS 6073, it requires 7 N/mmp2s as a minimum capacity to act as load bearing brick, while control brick shows 6.8 N/mmp2s the clamshell replaced brick, 16 N/mmp2s achieved the minimum compressive strength and exceed the compressive strength of control mixtures .The result of the study revealed that the introduction of clam shell in sand brick improve some of the properties of the sand brick compared to control brick and its potential to be a good load bearing wall.